Development of Local Wisdom-Based Blended Learning Programs to Improve Students’ Learning Outcomes and Communication Skills - Sari, Indra Kartika; Isdaryanti, Barokah; Ellianawati, Ellianawati (FKIP Universitas Lampung, 2022)
Development of Local Wisdom-Based Blended Learning Programs to Improve Students' Learning Outcomes and Communication Skills. Objectives: This study aimed to develop a blended learning program based on local wisdom for improving students' learning outcomes and communication skills. Methods: This development research was adapted from Dick and Carey, namely ADDIE. This study used data analysis techniques to convert quantitative data to qualitative data. Findings: All developed products got a score in valid category and practically category. The learning outcomes in the cognitive domain can be seen from the N-gain value of 0.71; it is enough effective category. The learning outcomes of the affective domains achieved the KKM score of 84% and the students who were incomplete of 16%. Students' communication skills average percentage scores on indicators of voice clarity 81%, writing clarity 74%, grammar 75%, performance 73%, expression 79%, and gestures 81%. Conclusion: The results of blended learning programs based on local wisdom can improve students’ learning outcomes and communication skills. Keywords: development, blended learning, local wisdom, learning outcomes, communication skills.DOI: http://dx.doi.org/10.23960/jpp.v12.i1.202226